Floral Nectary Morphology and Proteomic Analysis of Nectar of Liriodendron tulipifera Linn. - Zhou, Yanwei; Li, Meiping; Zhao, Fangfang; Zha, Hongguang; Yang, Liming; Lu, Ye; Wang, Guangping; Shi, Jisen; Chen, Jinhui (Frontiers in Plant Science, 2016)
Nectar is a primary nutrient reward for a variety of pollinators. Recent studies have demonstrated that nectar also has defensive functions against microbial invasion. In this study, the Liriodendron tulipifera nectary was first examined by scanning electron microscopy, and then the nectar was analysed by two-dimensional gel electrophoresis and liquid chromatography–tandem mass spectrometry, which led to identification of 44 nectar proteins involved in various biological functions. Bioinformatic analysis was then performed on an identified novel rubber elongation factor (REF) protein in L. tulipifera nectar. The protein was particularly abundant, representing ~60% of the major bands of 31 to 43 kDa, and showed high, stage-specific expression in nectary tissue. The REF family proteins are the major allergens in latex. We propose that REF in L. tulipifera nectar has defensive characteristics against microorganisms.